2022
DOI: 10.1021/acs.cgd.2c00661
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Physicochemical, and Biopharmaceutical Properties of Cocrystals with RS- and R-Praziquantel─Generation and Prolongation of the Supersaturation State in the Presence of Cellulosic Polymers

Abstract: Two novel cocrystals of the pharmaceutically active enantiomer R-Praziquantel (R-PZQ) were formed with glutaric acid (R-PZQ/GA) and succinic acid (R-PZQ/SA) in a 1:1 stoichiometric ratio by liquid-assisted mechanical grinding. The characterization of the cocrystals by structural and physicochemical methods revealed properties distinct from the cocrystal analogues with racemic PZQ, i.e., RS-PZQ/GA and RS-PZQ/SA, reported previously in the literature. However, all four cocrystals exhibit improved intrinsic disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
(222 reference statements)
0
7
0
Order By: Relevance
“…In the solid, PZQ and MA molecules alternate into racemic H-bonded chains along the b axis of the orthorhombic Pbca unit cell, with the acidic oxygen of the carboxylic acid bridging between two different carbonyl oxygen atoms of two PZQ racemes. Such a monodentate synthon has been previously described as a “type III” by Herrera-Ruiz and Höpfl . The hydroxyl group of MA acts as a H-bond donor in an intramolecular H-bond for the adjacent carboxylic group (Figures and S2), while it acts as an acceptor in an additional H-bond with another MA from the nearest chains that are aligned in an antiparallel orientation in the crystal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the solid, PZQ and MA molecules alternate into racemic H-bonded chains along the b axis of the orthorhombic Pbca unit cell, with the acidic oxygen of the carboxylic acid bridging between two different carbonyl oxygen atoms of two PZQ racemes. Such a monodentate synthon has been previously described as a “type III” by Herrera-Ruiz and Höpfl . The hydroxyl group of MA acts as a H-bond donor in an intramolecular H-bond for the adjacent carboxylic group (Figures and S2), while it acts as an acceptor in an additional H-bond with another MA from the nearest chains that are aligned in an antiparallel orientation in the crystal.…”
Section: Resultsmentioning
confidence: 99%
“…Such a monodentate synthon has been previously described as a “type III” by Herrera-Ruiz and Höpfl. 33 The hydroxyl group of MA acts as a H-bond donor in an intramolecular H-bond for the adjacent carboxylic group ( Figures 1 and S2 ), while it acts as an acceptor in an additional H-bond with another MA from the nearest chains that are aligned in an antiparallel orientation in the crystal.…”
Section: Resultsmentioning
confidence: 99%
“…It has been extensively reported that utilization of various pharmaceutically acceptable polymers (e.g., HPMC, PVP, and PEG) can effectively delay or suppress nucleation of drug compounds from supersaturated aqueous solutions and, therefore, inhibit precipitation of a poorly soluble component, improving the solution stability of a cocrystal. [70][71][72][73][80][81][82][83][84][85][86] In this study, we employed HPMC, a biocompatible polymer commonly used in the development of cocrystal formulations, 77 as a Nil precipitation inhibitor. Preliminary solubility studies have shown that HPMC at 0.1% concentration had virtually no effect on the thermodynamic solubility of Nil form I.…”
Section: Aqueous Solubility and Dissolution Studies Of [Nil + Adn] (1...mentioning
confidence: 99%
“…Finally, focusing the attention, once again, on PZQ-GLU plus also PZQ-SUC cocrystals, the same scientific group reported two novel cocrystals obtained through LAG in the presence of the above-mentioned coformers ground with enantiomerically pure (R)-PZQ in a 1:1 molar ratio [ 67 ]. The new cocrystals (i.e., (R)-PZQ-GLU and (R)-PZQ-SUC) were deeply characterized and compared with previously reported analogous cocrystals obtained with racemic PZQ (hereinafter referred as (RS)-PZQ-GLU and (RS)-PZQ-SUC), pure (R)-enantiomer hemihydrate (i.e., (R)-PZQ-HH), and pristine (RS)-PZQ.…”
Section: Pzq Multicomponent Solid Formsmentioning
confidence: 99%